Pengembangan Usaha Mikro, Kecil, dan Menengah Dalam Meningkatkan Perekonomian di Sektor UMKM Sentra Wisata Kuliner Dharmahusada Kota Surabaya - Husendi, Putri Aprilia Aini; Widiyarta, Agus (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The problem statement of this research pertains to the enhancement of micro, small, and medium-sized enterprises (MSMEs) to foster economic growth within the culinary tourism hub of Dharmahusada, Surabaya. This study aims to provide a descriptive account of the Development of Micro, Small, and Medium-Sized Enterprises in Elevating the Economic Landscape within the MSME Sector of the Culinary Tourism Hub in Dharmahusada, Surabaya. Employing a qualitative methodology with a descriptive approach, the research delves into the strategies employed for business development in boosting the economic facet of the MSME sector within the Dharmahusada Culinary Tourism Hub in Surabaya.The findings of the research underscore that the Surabaya City government has formulated rational, proportionate, and well-organized policies for the organization and provision of space for street food vendors within the Dharmahusada Culinary Tourism Hub. However, the implementation of these policies is impeded by various challenges, including inadequate dissemination of information, limited access to information, and insufficient support or guidance. To address these issues, effective dissemination of information concerning tax incentives for MSMEs, the establishment of comprehensive information systems, the creation of centers for consultation and development of MSMEs, as well as the establishment of a joint marketing system, are imperative. Keywords: Strategies for MSME Development; Economic Aspects of the MSME Sector; Surabaya City